The Analysis Of Satisfaction On Digital Business Sector: Expectation Confrimation Model Validation - Mohammad Fahmi Arkanuddin; Muhammad Abi Firmansyah; Muhammad Banu Fakhruddin; Citranti Hanifah Dewani; Trijatmi Erawati Kridaningsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This research aims to analyze the effect of satisfaction toward technology continuance intention on digital, business sector, expectation confirmation model validation. Using for quantitative approach and the instruments of distributing questionnaires and taking samples of 100 respondent and for using analysis tools SEM-Amos. Perceived of usefulness had affected directly and not significantly to continuance intention estimate 0,072 and had affected indirectly and significantly through satisfaction estimate 0,521, in while satisfaction had affected directly and significantly on technology continuance intention estimate 0,896 with the CR value 6.241 > cut off value CR 1.69 and the probability value (p-value) estimate 0,001 < cut off p-value 0,05. Perceived of usefulness and confirmation had affected simultaneously and significantly toward continuance intention through satisfaction estimate 0,915. The result of research had shown that satisfaction had the important role for encouraging the users that they felt the technology had usefulness for fulfill their needs, so the users still keep going for using the continuance intention on digital business sector, so it’s grew prospectively in the future.